The influence of Rhyzopertha dominica (F.) on the technological quality of cereal grains treated with diatomaceous earth. (January 2021) - Perišić, Vesna; Vuković, Slavica; Perišić, Vladimir; Luković, Kristina; Vukajlović, Filip; Hadnađev, Miroslav; Dapčević-Hadnađev, Tamara
Abstract: Laboratory bioassays (temperature 26 ± 1 °C and 60 ± 5% r. h.) were performed to evaluate the insecticidal effect of three different diatomaceous earths (DE) against Rhyzopertha dominica (F.) in wheat, triticale and rye. In order to achieve this, the amount of damaged kernels, amount of debris, wet gluten content, gluten index and rheological properties were assessed in infested samples, infested samples treated with DE Protect-It and two DEs originating from Serbia (S-1 and S-2) and were compared to control (uninfested) samples using Chopin Mixolab. The most susceptible to beetle infestation were rye sample and wheat variety Planeta. The lowest weight of damaged grain was found after applying DE Protect-It to all grain types. The amount of damaged kernels, the amount of debris and loss of mass were the highestin sample treated with DE S-2. While infestation resulted in increase in the amount of damaged kernels and debris and decrease in wet gluten content, and provoked weakening of gluten network structure as well as starch damage, an addition of DE, especially Protect-It, resulted in grain samples of similar technological quality to control (uninfested) sample. The susceptibility of different cereals used in breadmaking to infestation by R. dominica, as well as their response to the insecticidal effect of diatomaceous earth largely varied. Both cereal type and quality, as measured by wet gluten content and gluten index, influenced grain response to infestation. Insecticidal effect of diatomaceous earth, especially DE S-1and DE S-2, was the least effective in terms of triticale. These findings suggest that the application of DE in cereals storage management might largely be affected with grain type as well as grain composition and technological quality. Highlights: Wheat, triticale and rye responded differently to R. dominica infestation. Infestation resulted in weakening of gluten network and starch damage. Insecticidal effect of diatomaceous earths (DE) against R. dominica was found efficient. DE treatment was less efficient in triticale, rye and samples with higher gluten index.